2018
DOI: 10.5603/cj.2018.0147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-cardiovascular disease burden on thirty-day hospital readmission in heart failure patients

Abstract: Background: Little is known about the impact of non-cardiovascular disease (CVD) burden on 30--day readmission in heart failure (HF) patients. The aim of the study was to assess the role of non-CVD burden on 30-day readmission in HF patients. Methods: We analyzed the effect of non-CVD burden by frequency of ICD-9 code categories on readmissions of patients discharged with a primary diagnosis of HF. We first modeled the probability of readmission within 30 days as a function of demographic and clinical covariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Up to 25% of HF, patients may be readmitted within 30 days of discharge, with an additional mortality risk of ~10% 4‐7 . In the past few years, multiple HF risk‐prediction models have been proposed to identify HF patients at highest risk of 30‐day readmission or death–with the focus on 30‐day outcomes, in part related to reporting standards and reimbursement penalties in the U.S 8‐11 . However, window of vulnerability is likely longer, with the spike in event rates occurring out 90 days post‐discharge and plateauing thereafter 5,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Up to 25% of HF, patients may be readmitted within 30 days of discharge, with an additional mortality risk of ~10% 4‐7 . In the past few years, multiple HF risk‐prediction models have been proposed to identify HF patients at highest risk of 30‐day readmission or death–with the focus on 30‐day outcomes, in part related to reporting standards and reimbursement penalties in the U.S 8‐11 . However, window of vulnerability is likely longer, with the spike in event rates occurring out 90 days post‐discharge and plateauing thereafter 5,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic heart failure (HF) is considered a global pandemic with survival outcomes as malignant as some common cancers [1]. The progression of HF, worsening of symptoms and increasingly fre-quent hospitalizations negatively influence patient functional ability and health-related quality of life (QoL) [2][3][4][5]. Depression is one of the most important factors determining QoL in HF patients, this also contributes to social isolation [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…18 Numerous study authors have identified both clinical and nonclinical factors associated with HF 30-day all-cause readmission. Clinical factors include multimorbidity, 8,19,20 respiratory disease, renal failure, diabetes, 8,[19][20][21] depression, and anxiety. 8,20 Heart failure in isolation is rare; multimorbidity complicates the clinical management 20 and poses challenges as patients attempt to recognize symptom exacerbation.…”
mentioning
confidence: 99%
“…8,20 Heart failure in isolation is rare; multimorbidity complicates the clinical management 20 and poses challenges as patients attempt to recognize symptom exacerbation. 22 Nonclinical and sociodemographic factors that have been shown to predict 30-day all-cause readmission include previous hospitalization for HF, 8,21 longer length of stay on index admission, 19,23 male gender, 3,[19][20][21]23,24 age older than 60 years, 3,[19][20][21]23,24 Medicare coverage, 8,19,25 being retired or unemployed, 23,25 and living alone. 20,24,25 Authors of recent studies suggest that race may be dependent on the patient population studied; for example, some identify Black race 8,19,25 as a predictor of readmission, whereas others report White race 21,23,24 as a readmission predictor.…”
mentioning
confidence: 99%